Style and alignment in information-seeking conversation - Thomas, Paul; Czerwinski, Mary; McDuff, Daniel; Craswell, Nick; Mark, Gloria (Proceedings of the Conference on Computer-Human Information Interaction and Retrieval, 2018)
Analysis of casual chit-chat indicates that differences in conversational style—the way things are said—can significantly impact a participants' impressions of the conversation and of each other. However, prior work has not systematically analyzed how important style is in task-oriented, information-seeking exchanges of the sort we might have with a conversational search agent. We examine recordings from the MISC data set, where pairs of "users" and "intermediaries" collaborate on information-seeking tasks, and look for indications of style which can be computed at scale. We find that stylistic markers identified by Tannen in casual chat do exist in information-seeking dialogue, and that participants can be arranged along a single stylistic dimension: "considerate" to "involved". This labelling for style needs no manual intervention. Furthermore, we find that there is no clear best style; but that differences in style, previously thought to impede communication, are only a problem for shorter tasks. This result is likely due to alignment of conversational style over the course of an interaction.